2019
DOI: 10.1590/0370-44672017720169
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of iron ore tailings in the production of geopolymer mortars

Abstract: A great variety of silica and alumina-rich materials have been investigated in the production of alkaline activated binders (or geopolymers) with low environment impact, e.g. low CO 2 emissions. Geopolymer mortars and concretes may be more environmentally friendly if not only Portland cement but also natural aggregates (sand, gravel) are replaced with waste materials. This article presents results of geopolymers made with tailings from the iron mining industry. The geopolymer matrices are composed of metakaoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Borges et al [17] concluded that iron ore tailings may be suitable to produce mortar and concrete, but they recommended further studies to carry out long-term durability tests of these materials [17]. For them, geopolymers composed of up to 50% of iron ore tailings from jig and spiral classification processes are as dense as geopolymers produced with natural quartz aggregate, and, for higher percentages, the former is denser than the latter.…”
Section: Geopolymer Mortars Using Iron Ore Tailingsmentioning
confidence: 99%
“…Borges et al [17] concluded that iron ore tailings may be suitable to produce mortar and concrete, but they recommended further studies to carry out long-term durability tests of these materials [17]. For them, geopolymers composed of up to 50% of iron ore tailings from jig and spiral classification processes are as dense as geopolymers produced with natural quartz aggregate, and, for higher percentages, the former is denser than the latter.…”
Section: Geopolymer Mortars Using Iron Ore Tailingsmentioning
confidence: 99%
“…Mine tailing as a replacement of fine aggregate in mortar and concrete has been studied widely, mainly due to its particle size and specific gravity. Borges et al [22] reported that though the use of iron tailing as sand has no effect on strength properties, it affected the durability due to increased porosity and water absorption. Wang et al [13] studied the freeze thaw performance of mortar samples with graphite mine tailings as fine aggregates.…”
Section: Fine Aggregatementioning
confidence: 99%
“…and aerated concrete [8][9][10]. However, the current research mainly focuses on IOT waste rock as concrete aggregate, which largely reduces the admixture of IOTs in concrete, limiting the application value of ultrafine IOTs, while powdered IOTs are more likely to cause dust and other environmental problems [11][12][13][14]. Therefore, in order to make full use of ultrafine IOTs and produce high value-added products, IOTs can be developed as supplementary cementitious materials (SCMs) for concrete, which further reduces the cost of producing both cement and concrete products, and achieves the purpose of multi-functionality between the utilisation of solid waste resources and the green production of concrete products [15][16][17].…”
Section: Introductionmentioning
confidence: 99%